2009
DOI: 10.1007/s11249-009-9468-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internal Lubricants (PTFE and Silicon Oil) in Short Carbon Fibre-Reinforced Polyimide Composites on Performance Properties

Abstract: Short carbon fibre-reinforced thermoplastic polyimides (30 wt%) often show high and unstable coefficients of friction. In this study, the effects of internal lubrication by polytetrafluoroethylene (PTFE) (15 wt%) or silicon oil (15 wt%) have been investigated using a reciprocating cylinder-on-plate test under 50-100 N normal loads and 0.3-1.2 m/s sliding velocities. The sliding mechanisms are discussed by considering mechanical and thermochemical modifications. The PTFE additives provide lowest coefficients of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…Figure 5 shows the FTIR spectra, XPS survey spectra and TGA curves of Si-TPI. In Figure 5(a), it seemed that there were no obvious differences between PI and Si-TPI, except the characteristic vibration of saturated CAH at 2963 cm 21 in ACH 3 which are only present in UMIDA. At the same time, in Figure 5(b), Si element was not found on the surface of PI0 but appeared on Si-TPI.…”
Section: Resultsmentioning
confidence: 97%
“…Figure 5 shows the FTIR spectra, XPS survey spectra and TGA curves of Si-TPI. In Figure 5(a), it seemed that there were no obvious differences between PI and Si-TPI, except the characteristic vibration of saturated CAH at 2963 cm 21 in ACH 3 which are only present in UMIDA. At the same time, in Figure 5(b), Si element was not found on the surface of PI0 but appeared on Si-TPI.…”
Section: Resultsmentioning
confidence: 97%
“…The thermal stability of the microcapsules containing methyl silicone oil decreases, which directly leads to the poor heat resistance of binary composites compared to pure polyurethane, as shown in Figure . The curve showed that the large mass loss was at 300 to 450 °C because of the fact that the crosslinked structure of melamine‐formaldehyde resin was destroyed and the mass loss at 500 °C was due to the thermal decomposition of the methyl silicone oil . After SCFs added, the initial decomposition temperature of the ternary composites increased with the increase of SCFs content.…”
Section: Resultsmentioning
confidence: 99%
“…The curve showed that the large mass loss was at 300 to 450 8C because of the fact that the crosslinked structure of melamineformaldehyde resin was destroyed and the mass loss at 500 8C was due to the thermal decomposition of the methyl silicone oil. 19 After SCFs added, the initial decomposition temperature of the ternary composites increased with the increase of SCFs content. For the comparison of carbon residue rate, the residual carbon rate of the ternary composites increase, it was mainly due to the fact that the high heat resistance of the carbon fiber contribute to the good heat resistance of composites.…”
Section: Thermal Properties Of Ternary Compositementioning
confidence: 99%
“…Generally speaking, the carbon fiber additives can improve the wear resistance of polymeric matrix through increasing the loading capacity , while their lubricity is ambiguous under different conditions. When perpendicular to the sliding plane and sliding direction, the carbon fiber leads to high coefficient of friction, while it may result in low friction coefficient in parallel to orientation . According to Li et al , the incorporation of a certain amount of carbon fiber can greatly enhance the wear resistance but either increase or reduce the friction coefficient of CF/PI composites at room temperature (RT).…”
Section: Introductionmentioning
confidence: 99%